A Comprehensive Guide to Understanding and Applying Descriptive Statistics in Data Analysis - Rega Priandanagari Gevisa; Kurniati Kurniati (LPPM UIKA Bogor, 2024)
Statistics plays a central role in parsing and interpreting data, being an important foundation, especially in scientific disciplines In this digital age, where the volume of data is constantly increasing, an understanding of statistics is essential to draw meaningful insights from the information contained in the data. Descriptive statistics, using tables and charts, provide a clear and effective way to summarize and present data. Through table types such as frequency, classification, and contingency, as well as measures of data centering and dispersion, statistics enable a deeper understanding of patterns and variations within a dataset. Therefore, mastery of statistical concepts is key to optimizing the use of data in a decision-making context.